D-MannosE to prevent Recurrent urinary tract infecTions (MERIT): protocol for a randomised controlled trial - Franssen, M; Cook, J; Robinson, J; Williams, N; Glogowska, M; Yang, Y; Allen, J; Butler, CC; Thomas, N; Hay, A; Moore, M; Hayward, G (BMJ Publishing Group, 2021)
Introduction Recurrent urinary tract infections (RUTIs) have a significant negative impact on quality of life and healthcare costs. To date, daily prophylactic antibiotics are the only treatment which have been shown to help prevent RUTIs. D-mannose is a type of sugar which is believed to inhibit bacterial adherence to uroepithelial cells, and is already being used by some women in an attempt to prevent RUTIs. There is currently insufficient rigorous evidence on which to base decisions about its use. The D-mannose to prevent recurrent urinary tract infections (MERIT) study will evaluate whether D-mannose is clinically and cost-effective in reducing frequency of infection and symptom burden for women presenting to UK primary care with RUTI. Methods and analysis MERIT will be a two-arm, individually randomised, double blind placebo controlled, pragmatic trial. Participants will be randomised to take D-mannose powder or placebo powder daily for 6 months. The primary outcome will be the number of medical attendances attributable to symptoms of RUTI. With 508 participants we will have 90% power to detect a 50% reduction in the chance of a further clinically suspected UTI, assuming 20% lost to follow-up. Secondary outcomes will include: number of days of moderately bad symptoms of UTI; time to next consultation; number of clinically suspected UTIs; number of microbiologically proven UTIs; number of antibiotic courses for UTI; quality of life and healthcare utilisation related to UTI. A within trial economic evaluation will be conducted to examine cost-effectiveness of D-mannose in comparison with placebo. A nested qualitative study will explore participants’ experiences and perceptions of recruitment to, and participation in a study requiring a daily treatment. Ethics and dissemination Ethical approval has been obtained from South West-Central Bristol Research Ethics Committee. Publication of the MERIT study is anticipated to occur in 2021. Trial registration number ISRCTN 13283516.